2009
DOI: 10.1097/prs.0b013e3181a07439
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of Postburn Antebrachial Contractures Using Pedicled Thoracodorsal Artery Perforator Flaps

Abstract: This study revealed that the pedicled thoracodorsal artery perforator flap is a suitable alternative for postburn elbow contractures. A very long pedicle can be obtained to transfer the flap to the antecubital area without tension. With its thin, pliable texture and large size, it adapts well to forearm skin and the donor-site scar is considered cosmetically acceptable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 33 publications
2
14
0
2
Order By: Relevance
“…Thinning of the flaps was observed in his patient series. Similarly, we found that pre‐expanded pedicled TDA perforator flaps were thinned in the presented series when we compared our previous experiences with the TDA perforator flap 1, 2…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Thinning of the flaps was observed in his patient series. Similarly, we found that pre‐expanded pedicled TDA perforator flaps were thinned in the presented series when we compared our previous experiences with the TDA perforator flap 1, 2…”
Section: Discussionsupporting
confidence: 64%
“…The TDA perforator flap has gained popularity among reconstructive surgeons for the reconstruction of burn contractures 1, 2, 5–7. The widespread use of the thoracodorsal artery perforator flap is attributable to its following some distinctive characteristics: the basic and reliable anatomy, the ability to be thinned without compromising its blood supply, the possibility of obtaining a long pedicle, the pliability of the flap, and the lack of significant donor site morbidity 1, 2, 5–7…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If left untreated in a growing child, severe contractures can even lead to secondary facial skeletal abnormalities, compounding the problem (Fricke et al,1996). In the extremities scar contracture can severely limit the mobility of limbs and digits, with crippling results (e.g., Uygur et al,2009). In the urogenital tract it can cause urethral stricture and interfere with sexual function.…”
Section: The Problem Of Scarmentioning
confidence: 99%
“…El colgajo de perforantes de la arteria tóraco-dorsal es un colgajo amplio y fino y la secuela que deja en la zona donante es escasa, pero en su recorrido puede sufrir torsiones, tensión, rotura del pedículo y dificultades de retorno venoso (3).…”
Section: Introductionunclassified